Aplicación de una auditoría de control interno, en la florícola “Rosely Flowers”, ubicada en el sector Laigua, cantón Latacunga, provincia del Cotopaxi, en el período 1 de enero al 31 de diciembre del 2014 - Pallo Cuchiparte, Gladys Ximena (2016)
The present reserch work was carried out in the Flowerly company "Rosely Flowers”, with the objective of aplicate an internal control audit for to measure the level of compliance and efficiency of the internal control system and the scope of objectives and goals, for this purpose we used the inductive method, deductive, observation, descriptive, also applied techniques such as interview and surveys, which served as aid for the collection of information, with the aim of knowing the current situation. in the flower was implemented an audit of internal control, to each of the departments in the period 1st january to 31st december 2014". This audit allows you to assess and detect possible shortcomings and is designed to obtain a reasonable certainty about the level of compliance with the control of activities and duties manual….